Adaptor protein Ruk/CIN85 modulates manifestation of cancer stem cells (CSCs) features in mouse breast adenocarcinoma 4T1 cells - Horak, I.R.; Pasichnyk, G.V.; Gerashchenko, D.S.; Knopfova, L.; Borsig, L.; Drobot, L.B. (Reports of the National Academy of Sciences of Ukraine, 2018)
Using mouse breast adenocarcinoma 4T1 cells with stable overexpression or knockdown of adaptor protein Ruk/CIN85, its contribution to the manifestation of cancer stem cells features was estimated. It was demonstrated that the expression levels of reprogramming factors Klf4, Pou5f1/Oct4 and Nanog, as well as CSCs surface markers Cd44 and Cd24, depended on Ruk/CIN85 expression level: increased in the case of up-regulation and decreased in the case of down-regulation. It was found that the transcriptome patterns in 4T1 subclones with different expression levels of Ruk/CIN85 correlated with their ability to form mammospheres.